Whistleblowing as a means for compelled governance in corporate institutions - Hazlina Shaik Md Noor Alam (Penerbit Universiti Kebangsaan Malaysia, 2017)
Many critics argue that corporate accountability measures have become corporate public relations tools used to create a positive corporate image. This is because pressures generated by the ‘ethical’ investor community and other shareholders also contributed to the proliferation of voluntary measures and in today’s competitive world, a positive image as a responsible company adds significant value to a company’s business along with its reputation and it also helps in managing various risks. This area needs to be carefully treaded on, as it is a minefield filled with potential disasters that could implode with one wrong step. In Malaysia, the debate surrounding whistleblowing as a means to promote corporate accountability rages on. One of the biggest issues that whistleblower protection faced was that it must cover both local and multinational corporations. Whistleblower protection mechanisms should also already be implemented in such companies. The push could be attributed to a variety of reasons, among them being the ever-evolving nature of the world’s perception towards whistleblowers.